2012
DOI: 10.1371/journal.pone.0039714
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Kif26b Promotes Its Polyubiquitination and Subsequent Proteasomal Degradation during Kidney Development

Abstract: Kif26b, a member of the kinesin superfamily proteins (KIFs), is essential for kidney development. Kif26b expression is restricted to the metanephric mesenchyme, and its transcription is regulated by a zinc finger transcriptional regulator Sall1. However, the mechanism(s) by which Kif26b protein is regulated remain unknown. Here, we demonstrate phosphorylation and subsequent polyubiquitination of Kif26b in the developing kidney. We find that Kif26b interacts with an E3 ubiquitin ligase, neural precursor cell ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…To demonstrate the utility of KIF26B-C as a biochemical tool for dissecting the WNT5A-KIF26B signaling cascade, we tested several candidate molecules, focusing on the role of kinases. Glycogen synthase kinase 3 (GSK3), casein kinase (CK) and cyclin-dependent kinase (CDK) were previously implicated in WNT5A signaling or KIF26B regulation, but whether these kinases are specifically involved in WNT5A-dependent degradation of KIF26B has not been tested [ 23 , 24 , 25 , 26 ]. To investigate the role of these candidate kinases, we applied pharmacological inhibitors of these kinases to the GFP-KIF26B-C reporter cells and assessed the effects of these treatments on the ability of WNT5A to induce reporter degradation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To demonstrate the utility of KIF26B-C as a biochemical tool for dissecting the WNT5A-KIF26B signaling cascade, we tested several candidate molecules, focusing on the role of kinases. Glycogen synthase kinase 3 (GSK3), casein kinase (CK) and cyclin-dependent kinase (CDK) were previously implicated in WNT5A signaling or KIF26B regulation, but whether these kinases are specifically involved in WNT5A-dependent degradation of KIF26B has not been tested [ 23 , 24 , 25 , 26 ]. To investigate the role of these candidate kinases, we applied pharmacological inhibitors of these kinases to the GFP-KIF26B-C reporter cells and assessed the effects of these treatments on the ability of WNT5A to induce reporter degradation.…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note that Terabayashi and colleagues previously reported that the C-terminus of KIF26B mediates CDK-induced degradation of KIF26B [ 26 ]. In addition, the authors demonstrated that CDK-dependent phosphorylation of two specific amino acid residues in KIF26B, Thr-1859 and Ser-1962, promotes the recruitment of the E3 ubiquitin ligase Nedd4 to KIF26B [ 26 ]. Collectively, this study and our present study support the crucial role of the KIF26B C-terminus in determining the stability of the KIF26B protein.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that phosphorylation of Kif26b by other cellular kinases is involved in Wnt5a-dependent regulation of Kif26b. Interestingly, a previous study showed that cyclin-dependent kinase (CDK) phosphorylates Kif26b on multiple serine and threonine sites and that these phosphorylation events play a critical role in controlling the stability of Kif26b by recruiting the E3 ubiquitin ligase Nedd4 ( Terabayashi et al, 2012 ). It will be important in future studies to test whether these mechanisms, as well as the additional phosphorylation sites identified in our proteomic screens, are required for Wnt5a regulation of Kif26b degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, it was reported that at this site, integrin α8β1 is localized, which binds to nephronectin on the basal lamina covering epithelial stem cells [ 49 51 ]. In addition, the micro-tubule-dependent motor protein kinesin (KIF26B) is established here to control cell attraction, signal transduction, and developmental patterning [ 52 54 ].…”
Section: Reviewmentioning
confidence: 99%